Mean value and velocity variation of ions in different magnetic field at constant obliqueness - Adhikari, Bhesh Raj (Himalayan Physics, 2023)
The variation of mean values of different components of velocities concerning the magnetic field has been numerically investigated using a kinetic trajectory simulation model at a constant angle and electric field. At an angle of 30◦, mean values of different components of velocities at the different magnetic fields have been studied. As the magnetic field changes, the mean values of the three velocity components also change, but as the magnetic field increases from 2.5 mT to 5.5 mT mean value is almost constant.